Rare localization of tongue vascular lesion detected by multi‐parametric magnetic resonance imaging. Issue 1 (18th January 2022) - Gilardi, Antonio; Ralli, Massimo; Colizza, Andrea; Di Stadio, Arianna; Messineo, Daniela; Riminucci, Mara; Corsi, Alessandro; Greco, Antonio; de Vincentiis, Marco
Abstract: Hemangiomas are developmental vascular abnormalities that are common in the head and neck (60%), rare in the oral cavity, and uncommon in the tongue. A patient performed a multi‐parametric MRI, which characterized the lesion of his tongue, providing relevant information for diagnostic, therapeutic orientation, and realization of slight aggressive surgery with consequent excellent recovery. Abstract : Hemangiomas are developmental vascular abnormalities that are common in the head and neck (60%), rare in the oral cavity, and uncommon in the tongue. A patient performed a multi‐parametric MRI, which characterized the lesion of his tongue, providing relevant information for diagnostic, therapeutic orientation, and realization of slight aggressive surgery with consequent excellent recovery.